Diversity, Specificity, and Phylogenetic Relationships of Endohyphal Bacteria in Fungi That Inhabit Tropical Seeds and Leaves - Shaffer, Justin P.; Sarmiento, Carolina; Zalamea, Paul-Camilo; Gallery, Rachel E.; Davis, Adam S.; Baltrus, David A.; Arnold, A. Elizabeth (Frontiers in Ecology and Evolution, 2016)
Interactions between fungi and tropical trees help shape some of the most biodiverse communities on earth. These interactions occur in the presence of additional microbes that can modify fungal phenotypes, such as endohyphal bacteria (EHB). Here we examine the occurrence, diversity, and taxonomic composition of EHB in fungi that colonize seeds and leaves of plants in tropical forests. We use PCR and fluorescence microscopy to detect EHB in fungi, and a phylogenetic approach to explore evolutionary relationships among seed- and leaf-inhabiting fungi and their bacterial partners. Analyses focusing on two prevalent orders of fungi (Hypocreales and Xylariales) revealed that seed- and leaf-inhabiting fungi have a shared evolutionary history, yet differ in the prevalence, richness, and composition of their endohyphal symbionts. Phylogenetic analyses detected that the endohyphal habit is widespread, here encompassing members of seven phyla of bacteria (including three classes of Proteobacteria). Occurring in seed- vs. leaf-associated fungi has not resulted in detectable structure in the evolution of EHB, and no congruence was observed in the phylogenetic relationships of these apparently facultative, horizontally transmitted symbionts and their fungal hosts. Our results are consistent with multiple origins of fungus-bacterium associations and argue for evaluating focal pairs to determine how particular EHB affect the establishment or maintenance of fungal symbioses in seeds and leaves.